STATUS SOSIAL EKONOMI KELUARGA DAN POLA KONSUMSI MAKAN ANAK STUNTING DAN NORMAL DI SDN 157628 NAIPOSPOS BARAT 2 KECAMATAN SORKAM KABUPATEN TAPANULI TENGAH - Denima Sakti Pulungan; Etti Sudaryati; Zulhaida Lubis (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2017)
School-age children are the group that can not be ignored in national development for school-age children, especially primary school children is the development resources. Lack of nutrients will cause malnutrition status. If there is no improvement in energy consumption and adequate protein, the body will eventually be susceptible to disease infection then this may affect the growth process of the child's height so that the child has a body that tend to be short. This study aims to determine the socioeconomic status of the family and child stunting and consumption patterns of normal elementary school children Naiposposbarat 2 157628 Sorkam Sub District of Tapanuli Tengah. This research is a descriptive cross-sectional design. This research was conducted by calculating the adequacy of energy and protein, as well as the types of food from food consumption in children using a 24-hour food recall. Data collection is done by measuring the height of children as measured by tools microtoise, socioeconomic data interviews with questionnaires, and sheets FFQ. The results showed in general, based on the child's height for age there are 58.3% of children are short-child category, 41.7% of children whose normal category. The adequacy of child stunting macro nutrients namely energy adequacy amounted to 61.2% classified as good, and the amount of protein of 59.2% belong to the deficit. Macro nutrient adequacy normal child that energy sufficiency 54.3% classified as good, and the amount of protein of 14.3% belong to the deficit. Most children have a mother Stunting secondary education as much as 57.1%. While a child whose height is normal to have a mother as much as 48.6% secondary education. But there are as many as 11.4% of children whose height is normal to have a mother who Bachelor (S1). In addition, as many as 59.2% stunting Children have a father working as a farmer, and have an income below the minimum wage as much as 89.8%. Expected to families, especially mothers in order to provide a balanced nutritional intake so as to reduce the risk of stunting in children under five. In addition, the school suggested cooperation with attendant health centers to provide nutrition counseling school children as well as to the canteen to provide healthy snacks that contribute in adding to the nutrient intake of school children. Keywords: Stunting, Consumption Patterns, Socio-Economic Status